2005
DOI: 10.11646/zootaxa.1038.1.1
|View full text |Cite
|
Sign up to set email alerts
|

An electrophoretic comparison of the venoms of a colubrid and various viperid snakes from Turkey and Cyprus, with some taxonomic and phylogenetic implications

Abstract: Venom extracts obtained from a colubrid snake [Malpolon monspessulanus (Hermann)] and eight viperids [Vipera xanthina (Gray), Vipera ammodytes (Linnaeus), Vipera kaznakovi (Nikolsky), Vipera eriwanensis (Bonaparte), Vipera wagneri Nilson &Andrén, Vipera barani Böhme & Joger, Macrovipera lebetina lebetina (Linnaeus), Macrovipera lebetina obtusa Dwigubsky] distributed in Turkey and Cyprus were compared using polyacrylamide gel disc electrophoresis and densitometry analysis methods. The electrophoretic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The Ottoman Viper, Montivipera xanthina (Gray, 1849), an almost endemic species to Turkey, is known from the Central, Southern and Western Anatolia as well as some adjacent islands of Greece with vertical distribution to 2,000 m (Arikan et al 2005;Samy et al 2007;Göçmen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Ottoman Viper, Montivipera xanthina (Gray, 1849), an almost endemic species to Turkey, is known from the Central, Southern and Western Anatolia as well as some adjacent islands of Greece with vertical distribution to 2,000 m (Arikan et al 2005;Samy et al 2007;Göçmen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Anatolia have reported that, 15 venomous snake species (14 belonging to the family Viperidae) live in Anatolia [9]. Most of the venomous snake species in our country are the members of familia Viperidae [3].…”
Section: Discussionmentioning
confidence: 99%
“…Diff ering from other Vipera species, Macrovipera has fi nely divided supraocular plates. It has a subspecies endemic to Cyprus: Macrovipera lebetina lebetina (Arıkan et al, 2005 ;Göçmen et al, 2006 ). According to Baran ( 1976 ) and Başoğlu and Baran (1980), on the nearest mainland, Anatolia, lives Macrovipera lebetina obtusa .…”
Section: Viperidaementioning
confidence: 99%